Globalization and National Autonomy The Experience of Malaysia - Nelson, Joan M; Abdul Rahman Embong; Meerman, Jacob 1931- (Institute of Southeast Asian Studies, 2008)
"Half a century since Malayan independence in 1957, this collection of essays provides a welcome assessment of post-colonial, especially recent Malaysian policies on various fronts – development, 'looking East', 1997-98 crisis management, inter-ethnic redistribution, poverty reduction, trade, education, healthcare, globalization, Islam and national culture. This volume is a useful compendium for anyone seeking a broad overview of recent policy challenges and debates." – Jomo Kwame Sundaram, United Nations Assistant Secretary General for Economic Development